2017
DOI: 10.1093/alcalc/agx017
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for At-Risk Alcohol Consumption in Primary Care: A Randomized Evaluation of Screening Approaches

Abstract: Current Controlled Trials ISRCTN06145674.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Although screening based only on consumption may encourage the disclosure by parents, the findings of our DCE suggests that such an approach may not encourage social care practitioner’s to administer the tool as it does not seek to identify those parents whose drinking impacts upon the child. A move away from universal screening approaches recommended within health settings ( Coulton et al., 2017 ) towards targeted screening based upon observable problems within the family linked to alcohol may be necessary within a social care setting.…”
Section: Discussionmentioning
confidence: 99%
“…Although screening based only on consumption may encourage the disclosure by parents, the findings of our DCE suggests that such an approach may not encourage social care practitioner’s to administer the tool as it does not seek to identify those parents whose drinking impacts upon the child. A move away from universal screening approaches recommended within health settings ( Coulton et al., 2017 ) towards targeted screening based upon observable problems within the family linked to alcohol may be necessary within a social care setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there is insufficient evidence for an appropriate package that deals with comorbidity to scale-up 63 . Further, it has been shown that targeted screening misses out on the vast majority of patients that would be captured by universal screening 64 . Given the strong associations between harmful alcohol use and depression 65 , 66 , our protocol includes screening for depression and appropriate PHC-based management 67 69 or referral for those patients identified as screen positive by AUDIT-C.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GPs are often resistant toward universal, population-based approaches to SBI, presumably because of their laborious and time-consuming nature (16). Targeted or symptom-based approaches are more acceptable to GPs, and evidence suggests that targeted screening may be more efficient as it yields a higher prevalence of at-risk alcohol consumers than universal screening (17). Several strategies based on clinical relevance have been reported, e.g., semi-systematic method, pragmatic case findings, and relevance criteria, the latter focused on smoking but used a similar logic (13,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…To date however, most studies on SBI have focused on universal, widespread screening; far fewer studies have explored pragmatic (targeted or relevance-based) strategies to identifying hazardous or harmful drinkers in health care settings (17,18,22). One study compared universal screening of all patients vs. targeted screening focused on clinical relevance.…”
Section: Introductionmentioning
confidence: 99%